Study of the bioadsorption of heavy metals (Pb and Cu) in the waters of the Puyango river, using orange and apple banana peel - Bonilla Bermeo, Stefanie Michelle; Ortiz Sánchez, Eliza Yisabel; Vega Calero, Lady Germania (Ingeniería Química y Desarrollo, 2024)
Bioadsorbents are a new alternative to remove heavy metals, low cost compared to conventional methods. In this research work, the adsorption capacity was evaluated with a particle size of 0.3150 mm of apple and orange banana peel powder in water contaminated with lead and copper, carried out under normal conditions of ambient temperature and constant agitation at 100rpm The experimental procedure was based on two studies, the first one was carried out with 5%, 10%, 15% of each bioadsorbent powder of orange peel and apple banana with the 500ml sample of raw water. The second was based on the preparation of standard solutions with different concentrations starting with 5000ppm, 8000ppm and 10,000 ppm, with each bioadsorbent from which aliquots of 10ppm, 20ppm y 30ppm. The best removal results were obtained with the standard solution of 8000ppm, taking an aliquot of 30ppm. With the orange peel powder, a removal percentage of 91.60% of Lead and 78.11% of Collection was obtained, with a maximum adsorption capacity (q mg / g) 0.075 of Copper and 0.1284 of Lead. While with the apple tree banana, a removal percentage of 93.47% of Lead, and 85.71% of Copper with a maximum capacity (q mg / g) 0.082 of Copper and 0.1311 of Lead was obtained. In addition, with the mixture of both bioadsorbents, a removal percentage of 72.27% Copper was obtained, with a maximum capacity (q mg / g) 0.069 Copper.